Identification of a Dynamic Core Transcriptional Network in t(8;21) AML that Regulates Differentiation Block and Self-Renewal - Ptasinska, Anetta; Assi, Salam A.; Martinez-Soria, Natalia; Imperato, Maria Rosaria; Piper, Jason; Cauchy, Pierre; Pickin, Anna; James, Sally R.; Hoogenkamp, Maarten; Williamson, Dan; Wu, Mengchu; Tenen, Daniel G.; et al. (Cell reports (Cambridge), 2014)
Oncogenic transcription factors such as RUNX1/ETO, which is generated by the chromosomal translocation t(8;21), subvert normal blood cell development by impairing differentiation and driving malignant self-renewal. Here, we use digital footprinting and chromatin immunoprecipitation sequencing (ChIP-seq) to identify the core RUNX1/ETO-responsive transcriptional network of t(8;21) cells. We show that the transcriptional program underlying leukemic propagation is regulated by a dynamic equilibrium between RUNX1/ETO and RUNX1 complexes, which bind to identical DNA sites in a mutually exclusive fashion. Perturbation of this equilibrium in t(8;21) cells by RUNX1/ETO depletion leads to a global redistribution of transcription factor complexes within preexisting open chromatin, resulting in the formation of a transcriptional network that drives myeloid differentiation. Our work demonstrates on a genome-wide level that the extent of impaired myeloid differentiation in t(8;21) is controlled by the dynamic balance between RUNX1/ETO and RUNX1 activities through the repression of transcription factors that drive differentiation. [Display omitted] •RUNX1/ETO drives a t(8;21)-specific transcriptional network•RUNX1/ETO and RUNX1 dynamically compete for the same genomic sites•RUNX1/ETO targets transcription factor complexes that control differentiation•RUNX1/ETO depletion activates a transcriptional network dominated by C/EBPα Chromosomal rearrangements generate cancer-specific fusion genes that interfere with cell differentiation. Ptasinska et al. show that the most frequent fusion protein in acute myeloid leukemia (RUNX1/ETO) controls a cancer-propagating transcriptional network by binding to genomic sites in a dynamic equilibrium with wild-type RUNX1. Depletion of RUNX1/ETO installs a differentiation-promoting transcriptional network. Our findings demonstrate that the differentiation block in AML has a dynamic component as its core feature, which might provide a target for cancer-specific differentiation therapy.